Noise Exposure Alters Glutamatergic and GABAergic Synaptic Connectivity in the Hippocampus and Its Relevance to Tinnitus. (15th January 2021) - Zhang, Liqin; Wu, Calvin; Martel, David T.; West, Michael; Sutton, Michael A.; Shore, Susan E.
Abstract : Accumulating evidence implicates a role for brain structures outside the ascending auditory pathway in tinnitus, the phantom perception of sound. In addition to other factors such as age-dependent hearing loss, high-level sound exposure is a prominent cause of tinnitus. Here, we examined how noise exposure altered the distribution of excitatory and inhibitory synaptic inputs in the guinea pig hippocampus and determined whether these changes were associated with tinnitus. In experiment one, guinea pigs were overexposed to unilateral narrow-band noise (98 dB SPL, 2 h). Two weeks later, the density of excitatory (VGLUT-1/2) and inhibitory (VGAT) synaptic terminals in CA1, CA3, and dentate gyrus hippocampal subregions was assessed by immunohistochemistry. Overall, VGLUT-1 density primarily increased, while VGAT density decreased significantly in many regions. Then, to assess whether the noise-induced alterations were persistent and related to tinnitus, experiment two utilized a noise-exposure paradigm shown to induce tinnitus and assessed tinnitus development which was assessed using gap-prepulse inhibition of the acoustic startle (GPIAS). Twelve weeks after sound overexposure, changes in excitatory synaptic terminal density had largely recovered regardless of tinnitus status, but the recovery of GABAergic terminal density was dramatically different in animals expressing tinnitus relative to animals resistant to tinnitus. In resistant animals, inhibitory synapse density recovered to preexposure levels, but in animals expressing tinnitus, inhibitory synapse density remained chronically diminished. Taken together, our results suggest that noise exposure induces striking changes in the balance of excitatory and inhibitory synaptic inputs throughout the hippocampus and reveal a potential role for rebounding inhibition in the hippocampus as a protective factor leading to tinnitus resilience.